Factors influencing destination management organisation managers attitude and behavioural intention towards crisis planning / Mohmed Razip Hasan - Hasan, Mohmed Razip (2020)
In today’s competitive world, a tourist destination has to be resilient and strong against crisis that could destroy and compromise its positive image, economic and social potentials. Crisis has to be managed and needs proper effective plans, resources, readiness and leadership to be implemented. Tools, Standard Operating Procedures (S.O.Ps), manuals and guidelines on managing crisis have been introduced and practiced by relevant organisations and authorities for managers’ use including for crisis planning and response. All these challenges and availability of resources have has raised a question on how prepared destination managers in managing crisis. This thesis investigates the behavioural intentions of Destination Management Organisations (DMOs) managers towards undertaking crisis planning in their organisations. The study takes an explorative approach to identify several challenges in crisis planning and destination management. A literature review and interviews with travel industry professionals were conducted before an actual survey. The Theory of Planned Behaviour (TPB) was used to develop the framework underpinning the study based on three psychological factors: social influence (SI), perceived behavioural control (PBC) and past crisis experience (PE) and, two external contextual environmental factors i.e. the national culture of safety and security (NC) and operation in crisis prone locations (LO), and attitude (ATT) as a mediating variable, were investigated to determine their relationship with behavioural intention (BI) (dependent variable) to undertake crisis planning. A total of 400 questionnaires were distributed to DMO managers, with a 68.8 percent, or 275 usable responses for data processing and analyses using PLS-SEM. The result shows that all indicators used in the study have a high level capability to capture the issue of interest. The measurement models either first or second order, also shows acceptable level of capability to capture the study phenomena. The findings shows that perceived behaviour and location have significant effect on managers’ attitude. The social influence and national culture, however, give no effect toward managers’ attitudes. On the other hand, managers’ experience, social influence and attitudes have strong effects on their behavioural intentions towards crisis planning. If the average level of the above factors were high, then the average level of behavioural intention of the managers to perform will increase too. There was no effect of national culture and location on managers’ behavioural intention to undertake crisis planning. It is important for DMO managers to be exposed to crisis training, related committees and tools so that they are more prepared and ready to take responsibility in crisis planning.